Effects of Water Temperature on Breeding Phenology, Growth, and Metamorphosis of Foothill Yellow-Legged Frogs (Rana boylii): A Case Study of the Regulated Mainstem and Unregulated Tributaries of California's Trinity River - Wheeler, C. A.; Bettaso, J. B.; Ashton, D. T.; Welsh Jr, H. H. (River research and applications, 2015)
Many riverine organisms are well adapted to seasonally dynamic environments, but extreme changes in flow and thermal regimes can threaten sustainability of their populations in regulated rivers. Altered thermal regimes may limit recruitment to populations by shifting the timing of breeding activities and affecting the growth and development of early life stages. Stream‐dwelling anurans such as the foothill yellow‐legged frog (Rana boylii) in the Trinity River of northern California are model subjects for examining associations between water temperature and the timing of oviposition, hatching, and metamorphosis, and body condition and size of tadpoles and metamorphs. Breeding activity, hatching success, and metamorphosis occurred later, and metamorphs were smaller and leaner along the regulated and colder mainstem relative to six unregulated tributaries of the Trinity River. Persistently depressed summer water temperatures appear to play a seminal role in inhibited tadpole growth on the regulated mainstem and may be a causative factor in the pronounced decline of this population. Environmental flow assessments should account for the influence of the thermal regime on the development of vulnerable embryonic and larval life stages to improve outcomes for declining amphibian populations. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.